A kinetic study of esterification of naphthenic acids from a Colombian Heavy Crude Oil - Quiroga Becerra, Haydée; Mejía Miranda, Carlos; Laverde Cataño, Dionisio; Hernández López, Marian; Gómez Sánchez, Mauricio (CT&F - Ciencia, Tecnología y Futuro, 2012)
This article presents the kinetic study of the esterification reaction of naphthenic acids from a Colombian heavy crude oil, with a Total Acid Number (TAN) of 7,33 mgKOH/g, in a batch type reactor. Temperature was changed between 150 - 250°C while the ratio moles of methanol per mole of carboxylic groups, remained constant in 20:1. The reaction time was varied from 0 - 600 minutes. Reduction in the concentration of naphthenic acids in the reactor is determined by the measurement of Number Total Acid (TAN), ASTM D 664. Naphthenic acids were extracted from the crude and structurally characterized by Fourier Transform Infrared Spectroscopy (FTIR), Nuclear Magnetic Resonance (NMR) and Gel Permeation Chromatography (GPC). The esterified oil was analyzed by FTIR, to identify the variation of the main functional groups. After determining the activation energy, frequency factor and, reaction order, a kinetic law was proposed for the esterification of naphthenic acids in Colombian heavy oil. Finally, it was evaluated the effect of esterification of naphthenic acids on the corrosion of steel ASTM A106 Gr.B. The corrosion of steel was reduced from 34,16 to 3,08 mils per year, (mpy), after esterification of naphthenic acids.